Targeted Biopsy in the Detection of Prostate Cancer using an Office-Based MR-US Fusion Device - Sonn, Geoffrey A. (2012)
PURPOSE: Targeted biopsy of lesions identified on MRI may enhance detection of clinically relevant prostate cancers (CaP). We evaluate CaP detection rates in 171 consecutive men using MR-US fusion prostate biopsy. MATERIALS AND METHODS: Subjects underwent targeted biopsy either for active surveillance (N=106) or persistently elevated PSA but negative prior conventional biopsy (N=65). Before biopsy, each man had a multiparametric MRI at 3.0-Tesla. Lesions on MRI were outlined in 3D and assigned increasing cancer suspicion levels (image grade 1–5) by a uroradiologist. The Artemis biopsy tracking system was used to fuse the stored MRI with real-time ultrasound (US), generating a 3D prostate model on-the-fly. Working from the 3D model, transrectal biopsy of target lesions and 12 systematic biopsies were performed under local anesthesia in the clinic. RESULTS: 171 subjects (median age 65) underwent targeted biopsy. At biopsy, median PSA = 4.9 ng/ml and prostate volume = 48 cc. A targeted biopsy was three times more likely to identify cancer than a systematic biopsy (21% vs. 7%). CaP was found in 53% of men, 38% of whom had Gleason ≥7. 38% of men with Gleason ≥7 cancers were detected only on targeted biopsies. Targeted biopsy findings correlated with level of suspicion on MRI. 15 of 16 men (94%) with an image grade 5 target (highest suspicion) had CaP, including 7 with Gleason ≥7. CONCLUSIONS: Prostate lesions identified on MRI can be accurately targeted using MR-US fusion biopsy by a urologist in clinic. Biopsy findings correlate with level of suspicion on MRI.